Strategi Komunikasi Badan Penyuluh Pertanian dalam Meningkatkan Ketahanan Pangan di Aceh Tengah - Fachri, Husni; Rizha, Fachrur; Insan, Al (Universitas Gajah Putih, 2025)
This study aims to analyze the organizational communication strategies implemented by the Agricultural Extension Agency (BPP) in improving food security in Central Aceh Regency. In the context of climate change and economic challenges, the role of extension communication is very important in conveying innovations, knowledge, and sustainable agricultural practices to farmers. This study uses a descriptive qualitative method, data collected through in-depth interviews, observations, and documentation studies. Research informants were selected by purposive sampling, namely based on certain criteria relevant to the research objectives. The results show that the communication strategies used by the BPP of Central Aceh Regency include interpersonal communication, traditional and modern media, and a participatory approach that focuses on local wisdom within the community. This strategy has proven effective in improving farmers' knowledge, attitudes, and practices towards sustainable agricultural systems. The Agricultural Extension Agency makes communication not only a tool for conveying messages, but also a dialogue-based development strategy and empowerment of farming communities in Central Aceh Regency